The development of the Malaysian cultural elements framework / Noor A’yunni Muhamad ... [et al.] - Muhamad, Noor A’yunni; Tahir, Azian; Ramli, Ishak; S. Abu Bakar, Syed Alwi (Universiti Teknologi MARA, Perak, 2023)
Multiracial and multiethnic people make Malaysia what it is today: a diverse nation. The cultural traditions of Malaysia passed down from generation to generation, are heavily influenced by the country's origin story. Nevertheless, there aren't many authoritative sources or in-depth analyses that examine certain aspects of Malaysian culture. As a result, in-depth research into Malaysian cultural elements is required. This research aims to identify cultural aspects in general, while the second objective will focus on identifying the cultural elements of Malaysian culture. The method for identifying Malaysian culture is through an integrative literature review, in which all literature sources explaining culture as general and Malaysian cultural characteristics and elements are analyzed. The outcomes of this research indicate that the elements of Malaysian culture fall into material things such as architecture, archaeological artifacts, clothing, art, food, and pastimes. In contrast, non-material culture consists of norms, symbols, knowledge, ceremonies, festivals, language, social institutions, and social structure. Future scholars will refer to the research results from this study as a reference, particularly in the definition of Malaysian culture from diverse study disciplines. To have a more thorough and in-depth knowledge of Malaysian culture, it is recommended that future studies on Malaysian culture expand the factors that focus primarily on the development of Malaysian culture.